Amazon and Whole Foods: adventures in grocery shopping. Issue 2 (5th March 2020) - White, Susan
Abstract : Theoretical basis: This case focuses on valuation using various methods to price a firm. Students attempting this case should know the basics of how to value a company using discounted cash flow, comparable multiples and comparable transactions. Students will need to calculate the weighted average cost of capital using comparable companies and the capital asset pricing model and determine differences in value created by an acquisition vs a leveraged buyout (LBO). The case also discusses qualitative issues in mergers, such as fit between target and acquirer, integration issues, potential high debt from LBO. Research methodology: This case was library-researched, using Amazon and Whole Foods public filings and business press papers. Case overview/synopsis: Whole Foods Markets received a buyout offer from Amazon. Whole Foods could solicit offers from other firms, including firms more directly in the grocery business. Whole Foods also considered a management buyout or purchase by a private equity firm. Whole Foods had underperformed, with a falling stock price and reduced profitability. Amazon's bid was attractive, a premium of about 40 per cent over Whole Foods' pre-merger stock price. Whole Foods also wanted to consider issues such as culture. Whole Foods' strategy was to sell organic foods at premium prices, while Amazon was a retail discounter with a largely online business. Complexity academic level: This case is appropriate for graduate students at the end of their introductory course or for graduate or undergraduate students in a corporate finance elective, particularly a merger/restructuring elective. The case has been used in an advanced undergraduate finance elective, with a team presenting the case to the class, with remaining students in the class required to write case summaries and questions for the presenting group.